Sales Promotion Memoderasi Nilai yang Dirasakan dan Harga terhadap Revisit dengan Mediasi Kepuasan Konsumen Produk J.CO Donuts & Coffee - Dias Harum Suryani; Surya Bintarti; Joni Heruwanto (Departement of Mathematics Education, 2023)
The current generation prefers sweet foods, one of which is donuts which are easy to find in malls. Various kinds of donut shops spread across Indonesia, sales of J.CO Donuts & Coffee always occupy the first position based on Top Brand Award data. This study aims to examine the relationship between perceived value and price on repurchase intentions through the mediation of consumer satisfaction moderated by sales promotion. This research uses quantitative methods. Sampling in this study used the Non Probability Sampling Method with a purposive technique. The population used by the community in Bekasi district. The samples obtained were 100 respondents, with data analysis in this study using regression. This study proves that: 1) Perceived value can encourage consumers to repurchase J.CO Donuts & Coffee brand products. 2) The set price does not encourage consumers to repurchase J.CO Donuts & Coffee brand products. 3) The perceived value of J.CO Donuts & Coffee brand products creates a feeling of satisfaction, so that it can encourage consumers to repurchase the product J.CO Donuts & Coffee brand. 4) The price set by the producer for J.CO Donuts & Coffee brand products creates a feeling of satisfaction, so that it can encourage consumers to repurchase. 5) A high level of consumer satisfaction can encourage consumers to repurchase J.CO Donuts & Coffee brand products. 6) Sales Promotion can moderate the perceived value to encourage consumers to repurchase J.CO Donuts & Coffee brand products. 7) Sales promotion can moderate the set price to encourage consumers to repurchase J.CO Donuts & Coffee brand products.